PENGARUH KELINCAHAN ORGANISASI TERHADAP KINERJA BERKELANJUTAN MELALUI INOVASI PADA SEKTOR MANUFAKTUR DI KOTA BATAM - Sentoso, Antony; Reqha, Chairunisa Aj; Nelson, Alden (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
This research aims to measure and analyze the relationship between organizational agility, sustainability performance and Innovation Orientation which illustrates how organizations can leverage their capabilities to drive sustainability implementation and maintain their competitiveness in a business environment that will continue to grow rapidly. This study uses a quantitative method which tests the outer model of data validity test, and data reliability test using SmartPLS software. For data collection purposes, the researcher used a purposive sampling technique consisting of (150) employees at manufacturing companies in Batam City by distributing questionnaires in the form of G-form to the sample. The results of this research prove that Organizational Agility has an insignificant positive effect on Sustainability Performance, Organizational Agility has a positive and significant on Innovation Orientation, Innovation Orientation has an insignificant positive effect on Sustainability Performance, Organizational Agility has an insignificant positive effect on Sustainability Performance through Innovation Orientation